A creative research based on DANP and TRIZ for an innovative cover shape design of machine tools. (1st February 2017) - Hsieh, Ho-Nien; Chen, Jeng-Fung; Do, Quang Hung
ABSTRACT: Low profit margins, high costs in R&D, light-weighted, customer-oriented, and compressed time from development to market are the recent trends for the products in the machine tools industry. There is no single approach that can tackle these issues at the same time. In this research, we apply decision-making trial and evaluation laboratory-based analytic network process (DANP) and the theory of solving inventive problems (TRIZ) to the innovative design of machine tools so as to deal with the issues of high cost and compressed time from development to market simultaneously. In our proposed methods, the DANP is employed as a decision support tool that can adequately provide qualitative and subjective assessments under the multiple criteria decision-making environment, and the TRIZ can provide several techniques to facilitate problem-solving. Results show that after applying our suggested methods, the cost is reduced, the profit is greatly increased, and the average time from development to market is decreased from 42 days to 21 days.